2022
DOI: 10.1371/journal.pmed.1004046
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a brief group behavioural intervention on psychological distress in young adolescent Syrian refugees: A randomised controlled trial

Abstract: Background Millions of young adolescents in low- and middle-income countries (LMICs) affected by humanitarian crises experience elevated rates of poor mental health. There is a need for scalable programs that can improve the mental health of young adolescents. This study evaluated the effectiveness of a nonspecialist delivered group-based intervention (Early Adolescent Skills for Emotions (EASE)) to improve young adolescents’ mental health. Methods and findings In this single-blind, parallel, controlled tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…The intervention also comprises three group sessions for caregivers that teach coping skills, positive parenting, and inform them of the strategies taught to the adolescents. One initial trial of the EASE program randomised young adolescent Syrian refugees in Jordan to either EASE or Enhanced Usual Care, and found that three months after the intervention the adolescents reported greater reductions in internalising problems relative to those in usual care (Bryant et al, 2022b ). Although this study indicated support for the EASE program, further studies are needed to validate the robustness of this effect.…”
Section: The Emergence Of Scalable Interventionsmentioning
confidence: 99%
“…The intervention also comprises three group sessions for caregivers that teach coping skills, positive parenting, and inform them of the strategies taught to the adolescents. One initial trial of the EASE program randomised young adolescent Syrian refugees in Jordan to either EASE or Enhanced Usual Care, and found that three months after the intervention the adolescents reported greater reductions in internalising problems relative to those in usual care (Bryant et al, 2022b ). Although this study indicated support for the EASE program, further studies are needed to validate the robustness of this effect.…”
Section: The Emergence Of Scalable Interventionsmentioning
confidence: 99%
“…Only nine out of the twenty-five studies identified were rated as strong or moderate quality, and among these, only seven reported significant improvements in mental health outcomes, including depression, anxiety, or PTSD (21,26,32,33,37,43,44). Among these seven, four adopted a CBT-based approach (21,26,43,44), while two followed a mindfulness approach (33,37). The most frequently studied CBT-based intervention was TRT (26,43,49).…”
Section: Discussionmentioning
confidence: 99%
“…Several of the included studies trialled interventions with refugee populations (21,29,30,43,46,49,50). This area has a growing evidence base, considering that refugees are often supported in low-resource environments such as refugee camps, where accessing specialised support can be challenging even after achieving settled status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This feasibility trial and a simultaneous study in Jordan [ 23 ] were conducted in preparation for the first full-scale evaluations of EASE in Lebanon and Jordan [ 24 , 25 ]. Additional studies have been conducted in Tanzania [ 26 ] and Pakistan [ 27 ].…”
Section: Introductionmentioning
confidence: 99%